2022
DOI: 10.1155/2022/9222331
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of F-18 FDG Uptake in Colon Cancer after Bacterial Cancer Therapy Using Engineered Salmonella Typhimurium: A Preliminary In Vivo Study

Abstract: Purpose. Bacterial cancer therapy (BCT) research using engineered Salmonella typhimurium has increased in recent years. 2-Deoxy-2[18F] fluoro-D-glucose positron emission tomography (FDG PET) is widely used in cancer patients to detect cancer, monitor treatment responses, and predict prognoses. The aim of this pilot study was to investigate FDG uptake patterns in a mouse tumor model after BCT. Procedures. BCT was performed via the intravenous injection of attenuated S. typhimurium (SLΔppGpp/lux) into female mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In addition, (Chong et al., 2022 ) explored the uptake pattern of 18F‐fluoro‐D‐glucose (18F‐FDG) PET in mouse CT26 tumour models before and after BCT, which indicated that the higher the rate of FDG tumour uptake before BCT is, the better the BCT response is. FDG uptake pattern was associated with tumour volume change after BCT, so an assessment based on the FDG uptake can be used to evaluate the efficacy of BCT.…”
Section: Bacteria Imaging In Tumour Diagnosismentioning
confidence: 99%
“…In addition, (Chong et al., 2022 ) explored the uptake pattern of 18F‐fluoro‐D‐glucose (18F‐FDG) PET in mouse CT26 tumour models before and after BCT, which indicated that the higher the rate of FDG tumour uptake before BCT is, the better the BCT response is. FDG uptake pattern was associated with tumour volume change after BCT, so an assessment based on the FDG uptake can be used to evaluate the efficacy of BCT.…”
Section: Bacteria Imaging In Tumour Diagnosismentioning
confidence: 99%